Impact of age at diagnosis of metastatic breast cancer on overall survival in the real-life ESME metastatic breast cancer cohort. (August 2020) - Frank, Sophie; Carton, Matthieu; Dubot, Coraline; Campone, Mario; Pistilli, Barbara; Dalenc, Florence; Mailliez, Audrey; Levy, Christelle; D'Hondt, Véronique; Debled, Marc; Vermeulin, Thomas; Coudert, Bruno; et al.
Abstract: Background: Young age is a poor prognostic factor in early stage breast cancer (BC) but its value is less established in metastatic BC (MBC). We evaluated the impact of age at MBC diagnosis on overall survival (OS) across three age groups (<40, 40 to 60 and > 60 years(y)). Methods: ESME MBC database is a national cohort, collecting retrospective data from 18 participating French cancer centers between January 01, 2008 and December 31, 2014. Results: Among 14 403 women included, 1077 (7.5%), 6436 (44.7%) and 6890 (47.8%) pts were <40, 40–60 and > 60 y respectively. Pts <40 had significantly more aggressive presentations than other age groups: more frequent HER2+ (25.7 vs 15.3% in >60y) and triple negative subtypes (27.4 vs 14.6% in >60y), and more frequent visceral involvement (36.3 vs 29.8% in >60y). At a median follow-up of 48 months, median OS differed across age groups: 38.8, 38.4 and 35.6 months for pts <40, 40–60 and > 60y, respectively (p < 0.0001). Compared to pts <40y, older pts had a statistically significant higher risk of death (all causes of death included), although of limited clinical value (HR = 1.1, IC 95%:1.01–1.20). There was a significant trend for better OS in pts <40y with HER2+ and luminal diseases. A possible explanation is a greater use of anti-Her2 therapies as first-line treatments: 86.6, 81.9 and 74.9% for pts <40, 40–60 and > 60y, respectively (p < 0.0001). Conclusion: Although young age seems associated with more aggressive presentations at diagnosis of MBC, it has no deleterious effect on OS in this large series. Highlights: Young age is a poor prognosis factor in early stage breast cancer. Young age is associated with an aggressive presentation in metastatic breast cancer. Young age had no impact on overall survivall in metastatic breast cancer. Oppositely, older women (>60y) had a stightly poorer prognosis at the metastatic stage.